Predictors for occlusion of cerebral AVMs following radiation therapy : Radiation dose and prior embolization, but not Spetzler-Martin grade - Knippen, Stefan; Putz, Florian; Semrau, Sabine; Lambrecht, Ulrike; Knippen, Arzu; Buchfelder, Michael; Schlaffer, Sven-Martin; Struffert, Tobias; Fietkau, Rainer (Strahlentherapie und Onkologie, 2017)
BACKGROUND: Intracranial arteriovenous malformations (AVMs) may show a harmful development. AVMs are treated by surgery, embolization, or radiation therapy. OBJECTIVE: This study investigated obliteration rates and side effects in patients with AVMs treated by radiation therapy. METHODS: A total of 40 cases treated between 2005 and 2013 were analyzed. Single-dose stereotactic radiosurgery (SRS) was received by 13 patients and 27 received hypofractionated stereotactic radiation therapy (HSRT). In 20 patients, endovascular embolization had been performed prior to irradiation and 24 patients (60 %) had a history of previous intracranial hemorrhage. RESULTS: Treatment resulted in complete obliteration (CO) in 23/40 cases and partial obliteration in 8/40. CO was achieved in 85 % of patients receiving SRS compared to 44 % of those receiving HSRT. In the HSRT group, a first indication of an influence of AVM volume on obliteration rate was found. Equivalent 2 Gy fraction doses (EQD2) >70 Gy showed an obliteration rate of 50 %. Prior embolization was significantly associated with a higher portion of CO (p = 0.032). Median latency period (24.2 vs. 26 months) until CO was similar in both groups (SRS vs. HSRT). The rate of intracranial hemorrhage in patients with no prior bleeding events was 0 %. CONCLUSION: Excellent obliteration rates were achieved by SRS. Consistent with the literature, this data analysis suggests that the results of HSRT are volume-dependent. Furthermore, regimens with EQD2 doses >70 Gy appear more likely to achieve obliteration than schemes with lower doses. The findings indicate that radiation therapy does not increase the risk of bleeding. Prior embolization may have a good prognostic impact.
EVALuna2:32909